User-Generated Content: A Systematic Literature Review (SLR) Research - Suryatini, Ni Wayan; Juniman, Puput Tripeni; Riesardhy, Anastasia Winanti; Irwansyah, Irwansyah (UI Scholars Hub, 2025)
The advancement of technology has given rise to the phenomenon of user-generated content (UGC), which presents an intriguing subject for investigation through various perspectives. This paper aims to conduct an analysis of journal articles focusing on UGC within the context of the Instagram social media platform. To achieve this, the paper employs a systematic literature review (SLR) research method, adhering to the PRISMA protocol, focusing specifically on journal articles discussing UGC on Instagram. The literature search was conducted in April 2023 using the keywords